Determinan Kepatuhan Wajib Pajak Orang Pribadi di Kantor Pelayanan Pajak Kabupaten Gianyar - I Gusti Agung Bagus Dhimas Kustri Widyana; I Ketut Jati (Transpublika Publisher, 2025)
Taxpayers in Indonesia can calculate, remit and file taxes independently through the personal assessment system. Taxpayers' trust in this system is highly dependent on their level of loyalty. This study aims to identify the factors that influence the level of individual tax compliance at the Gianyar Primary Tax Office (KPP). Using a random sampling method, the study successfully collected 100 respondent samples. The research findings reveal that aspects of environment, understanding, awareness, and the application of tax sanctions comprehensively contribute to increasing individual compliance in fulfilling tax obligations. The results of the analysis reveal that increasing understanding at KPP has the potential to be significant in increasing taxpayer compliance. Such compliance is influenced by the existence of tax sanctions and the level of individual awareness. This study proves that there is a strong relationship between taxpayers' level of understanding and their compliance. In addition, a conducive environment and the proper application of sanctions can be a driving factor in increasing tax compliance.